THE NOUN PHRASE WITHIN THE LIGHT VERB CONSTRUCTIONS FROM A SYNTACTIC AND SEMANTIC POINT OF VIEW (Philological Studies, 2019)
This paper discusses the noun phrase (NP) within the light verb constructions (LVCs) from a syntactic and semantic point of view. From a syntactic point of view, by applying a series of tests and citing examples from English and Macedonian, it was demonstrated that the NP within the LVCs functions as a direct object. On the other hand, although the nominalization within the LVCs can be treated as nomen actionis, it seems that sometimes there are grounds to treat this noun as a resultative deverbal noun (i.e. a noun which is closer to the concept of nomen acti than to that of nomen actionis). The semantic role of the argument in DO position is regarded as proto-patient, but it should be taken into account that some arguments are closer to, while others are more distant from the prototypical patient.
Keywords: noun phrase, light verb constructions, nominalization